Short history of international affairs 1920 to 1939 - Gathorne-Hardy, G. M. (London, 1947)
The previous editions of this work inevitably suffered from the disadvantage that they dealt with an unfinished story, and with a moving tide of events which continued to flow while the final passages were being written. Thus, in 1938, it was only possible to include an account of the Munich negotiations in the form of a postscript, written after the whole book was already set up in page. I welcome the oppor tunity now afforded, of completing the narrative down to the outbreak of the present hostilities, thus extending the history to cover the whole of the defined period intervening between the two German wars. This has the further advan tage that the author has not on this occasion been compelled to wrestle with a slippery Proteus whose final form was still a matter for conjecture.
Keywords: World Politics